Utilization of Advance Technology and Techniques in Analysis of a Tall Structure - Manu Kumar Pandit; Dharmendra Prajapati; Anudeep Nema (International Journal of Scientific Research in Civil Engineering, 2022)
Now-a-days, the architects often prohibit the widths of the columns so that more free space is available and for the good aesthetic look of the building without columns protruding out of the walls and corners. Advances in structural members and techniques to resist lateral forces are generally used now days to pretend more stable and safe structure. In present work with the end goal to contrast fortified solid structure using traditional columns against structure designed with special shaped columns considering seismic loads on G+12 multi-story building having plan measurement 63.20mx29.50m m is displayed and dissected in Etab adaptation coordinated building outline programming. Proportionate static investigation and dynamic reaction range examination are performed on the structure.